Thermal environment barrier coating for small-thickness ceramic-based composite material as well as preparation method and application of thermal environment barrier coating
By using a combined structure of Si-HfO2-X bonding layer, Yb2Si2O7 environmental barrier layer and (RE1mRE21-m)2Zr2O7 thermal barrier surface layer on the ceramic matrix composite, the problem of excessive thickness of the existing thermal barrier coating is solved, low thickness, high bonding strength and excellent high-temperature corrosion resistance are achieved, the service stability of the material is improved and the weight of the parts is reduced.
Patent Information
- Application Number
- CN202411738917.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
The thickness of the thermal environment barrier coating for existing ceramic matrix composite materials is large, resulting in rapid accumulation of thermal stress during the hot and cold cycle, increasing the risk of coating peeling failure, and increasing the influence of material quality and throat area, affecting the engine power performance.
The combined structure of Si-HfO2-X bonding layer, Yb2Si2O7 environmental barrier layer and (RE1mRE21-m)2Zr2O7 thermal barrier surface layer was prepared by atmospheric plasma spraying and electron beam physical vapor deposition technology, and the thickness was controlled within 20-60μm, which improved the bonding strength with the substrate and the resistance to high-temperature corrosion.
The low thickness, high bonding strength and excellent high-temperature corrosion resistance of the thermal environment barrier coating for ceramic matrix composites are achieved, which extends the service stability of the material, reduces the weight of the part and reduces the impact of the coating on the throat area.
Smart Images

Figure CN119528591A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-temperature protective coating materials, and in particular relates to a thermal environment barrier coating for a small-thickness ceramic-based composite material and a preparation method and application thereof. Background Art
[0002] Silicon carbide fiber reinforced silicon carbide ceramic matrix composites (SiC f Compared with traditional high-temperature alloys, CMCs (SiC-CMCs) have the characteristics of low density, high specific strength, and excellent high-temperature mechanical properties. They are one of the key materials for achieving leapfrog development in aircraft engine performance. At present, the main challenge for the large-scale use of CMCs in aircraft engine hot end components is their poor environmental durability in the engine combustion environment. Since high-speed gas flow is rich in water vapor, the CMCs matrix will react with water vapor to generate volatile silicon hydroxide (Si(OH)4), causing a sharp decline in component size, stability and other performance.
[0003] The preparation of high-performance environmental barrier coatings (EBCs) on the surface of CMCs components is crucial to improving the operating temperature and service life of the material. The third-generation EBCs system of "Si bonding layer + Mullite intermediate layer + ytterbium silicate environmental barrier layer" proposed by NASA in the United States can be stably used for a long time below 1350°C. At present, it has basically met the high-temperature corrosion protection needs of various types of CMCs components. High-temperature corrosion generally includes corrosion such as water and oxygen under high-temperature conditions, CMAS, etc. Among them, dust in the atmosphere, such as volcanic ash, sand and dust and other environmental sediments, its main chemical composition is CaO-MgO-AlO 1.5 -SiO2, referred to as CMAS.
[0004] However, the thickness of the third-generation EBCs system is generally between 250 and 400 μm, which is relatively thick. On the one hand, the thicker the coating, the faster the thermal stress accumulates during the hot and cold cycle, increasing the risk of coating peeling failure. On the other hand, the increase in coating thickness will lead to an increase in the mass of CMCs components, which does not meet the design requirements of aircraft engine structure weight reduction. In addition, excessively thick coatings will inevitably reduce the throat area of CMCs components, which will have a certain impact on the engine power performance. Therefore, under the premise of not affecting the high-temperature corrosion resistance of EBCs, by modifying the composition and structure of existing EBCs, the thickness of the coating system can be minimized, which is of great significance to improving the performance of aircraft engines. Summary of the invention
[0005] In view of this, the present invention provides a thermal environment barrier coating for small-thickness ceramic-based composite materials and a preparation method and application thereof. The thermal environment barrier coating provided by the present invention has a relatively small thickness, a high bonding strength with the substrate, and excellent high-temperature corrosion resistance. While improving the service stability and reliability of CMCs components, it can reduce the weight of parts and reduce the influence of the coating on the throat area of parts.
[0006] The present invention provides a thermal environmental barrier coating for a small-thickness ceramic-based composite material, which comprises a bonding layer, an environmental barrier layer and a thermal barrier surface layer in sequence, wherein the bonding layer is composed of Si-HfO2-X, wherein X is any one of Y, Yb, Gd and Er, and the bonding layer is in contact with a substrate;
[0007] The composition of the environmental barrier layer is Yb2Si2O7;
[0008] The composition of the thermal barrier surface layer is (RE1 m RE2 1-m )2Zr2O7, where RE1 and RE2 are respectively one of Gd, Yb, La, Dy, Sm and Nd, and m is the atomic percentage.
[0009] Preferably, the molar ratio of Si, HfO2 and X in the bonding layer is 50-60:25-35:5-25.
[0010] Preferably, the thermal barrier surface layer has a columnar crystal structure.
[0011] Preferably, the thickness of the adhesive layer is 20-40 μm, the thickness of the environmental barrier layer is 30-50 μm, and the thickness of the thermal barrier surface layer is 40-60 μm.
[0012] The present invention provides a method for preparing a thermal barrier coating for a ceramic-based composite material with a small thickness as described above, comprising the following steps:
[0013] By means of thermal spraying and / or physical vapor deposition on the surface of the base material, the corresponding raw material powders are sequentially formed into a bonding layer, an environmental barrier layer and a thermal barrier surface layer, and after heat treatment, a thermal environmental barrier coating for a ceramic-based composite material with a small thickness is obtained.
[0014] Preferably, the bonding layer is formed by atmospheric plasma spraying, and argon and hydrogen are used as plasma during the spraying process. The flow rate of argon is 40-60L / min, the flow rate of hydrogen is 5-15L / min, the spraying distance is 80-150mm, the spraying current is 300-600A, and the powder feeding rate is 10-30g / min; the raw material powder is Si-HfO2-X powder with a particle size of 15-60μm.
[0015] Preferably, the environmental barrier layer is formed by atmospheric plasma spraying, and argon and hydrogen are used as plasma during the spraying process. The flow rate of argon is 40-80L / min, the flow rate of hydrogen is 5-15L / min, the spraying distance is 100-200mm, the spraying current is 500-800A, and the powder feeding rate is 10-30g / min; the raw material powder is Yb2Si2O7 powder with a particle size of 15-45μm.
[0016] Preferably, the thermal barrier surface layer is formed by electron beam physical vapor deposition, and the electron beam physical vapor deposition process comprises: m RE2 1-m )2Zr2O7 target material is loaded into an electron beam physical vapor deposition device, and a thermal barrier surface layer is formed on the surface of the environmental barrier layer by evaporating the target material. The evaporation current is 1.2-1.8A, the substrate temperature is 850°C-950°C, and the vacuum degree is 10 -3 Pa, the deposition time is 20 to 45 minutes.
[0017] Preferably, the matrix material is a ceramic-based composite material; the preparation method further comprises pre-treating the ceramic-based composite material, wherein the pre-treatment comprises one or more of cleaning, sandblasting and plasma jet heating;
[0018] The heat treatment temperature is 1100-1300° C. and the time is 8-16 hours.
[0019] The present invention provides the use of the thermal environment barrier coating as described above as a thermal protection coating on the surface of a ceramic-based composite material high-temperature component in an aeroengine.
[0020] Compared with the existing environmental barrier coating system, the thin-thickness thermal environmental barrier coating described in the embodiment of the present invention has a Si-HfO2-X bonding layer (X is any one of Y, Yb, Gd and Er), and sequentially includes a Yb2Si2O7 environmental barrier layer and a specific composition (RE1 m RE2 1-m )2Zr2O7 thermal barrier surface layer. In the Si-HfO2-X bonding layer described in the embodiment of the present invention, part of the HfO2 will react with SiO2 at high temperature to form a high-temperature thermally stable HfSiO4 phase. This phase has a "pinning" effect in the coating, which can deflect or even terminate microcracks, thereby increasing the service life of the coating. At the same time, X solid dissolves into part of the HfO2 lattice, causing HfO2 to transform from an m phase to a c phase. This phase has a lower thermal conductivity at high temperatures and can provide a certain thermal protection effect on substrates such as CMCs. The Yb2Si2O7 environmental barrier layer is disposed between the bonding layer and the thermal barrier surface layer, which is mainly beneficial in alleviating the accumulation of thermal stresses during hot and cold cycles. The (RE1 m RE2 1-m)2Zr2O7 thermal barrier surface layer has excellent high temperature corrosion resistance (water oxygen, CMAS, etc.) and low thermal conductivity, and can provide good high temperature corrosion protection for CMCs substrates, etc. The thermal environment barrier coating system described in the present invention has a small thickness, which is expected to reduce the weight of parts and reduce the impact of the coating on the throat area of parts while ensuring the service life of the hot end parts of ceramic matrix composite materials.
[0021] In addition, the present invention preferably adopts electron beam physical vapor deposition to prepare the thermal barrier surface layer, which can not only ensure that the coating has a lower surface roughness and a higher density, but also the coating surface layer has a columnar crystal structure and a higher strain tolerance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0023] Figure 1 It is a schematic cross-sectional structure diagram of a thermal barrier coating with a small thickness prepared on the surface of a ceramic-based composite material in one embodiment of the present invention;
[0024] Figure 2 is a flow chart of a method for preparing a thermal barrier coating with a small thickness according to an embodiment of the present invention;
[0025] Figure 3 This is the surface morphology of the small-thickness thermal barrier coating described in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the technical scheme of the present invention is now described in detail below in conjunction with specific embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0027] The present invention provides a thermal environmental barrier coating for a ceramic-based composite material with a small thickness, wherein the thermal environmental barrier coating comprises a bonding layer, an environmental barrier layer and a thermal barrier surface layer in sequence, wherein the bonding layer is composed of Si-HfO2-X, wherein X is any one of Y, Yb, Gd and Er, and the bonding layer is in contact with the substrate; the environmental barrier layer is composed of Yb2Si2O7; the thermal barrier surface layer is composed of (RE1 m RE2 1-m )2Zr2O7, where RE1 and RE2 are respectively one of Gd, Yb, La, Dy, Sm and Nd, and m is the atomic percentage.
[0028] The thermal environment barrier coating provided by the present invention has a relatively small thickness, a high bonding strength with the substrate, and excellent high-temperature corrosion resistance. While improving the service stability and reliability of CMCs components, it can reduce the weight of the parts and alleviate the influence of the coating on the throat area of the parts.
[0029] See also Figure 1 , which illustrates the cross-sectional structure of the thermal environmental barrier coating described in some embodiments; wherein 1 is a ceramic-based composite material matrix, 2 is a Si-HfO2-X bonding layer, 3 is a Yb2Si2O7 environmental barrier layer, 4 is (RE1 m RE21 -m )2Zr2O7 thermal barrier surface layer.
[0030] In the present invention, the matrix material is preferably a ceramic matrix composite matrix 1, i.e., a CMCs matrix. The present invention has no special restrictions on the specific composition of the matrix material, and any ceramic matrix composite matrix conventionally used in the art can be used, such as silicon carbide fiber reinforced silicon carbide, or other reinforcing fibers and silicon nitride and other ceramic matrices.
[0031] In the present invention, the base material is in contact with one side of the bonding layer in the coating, and the bonding layer is composed of Si-HfO2-X, which can be called Si-HfO2-X bonding layer, and has good bonding properties. In the Si-HfO2-X bonding layer 2 described in the embodiment of the present invention, X is a rare earth element selected from yttrium (Y), ytterbium (Yb), gadolinium (Gd), and erbium (Er), such as Si-HfO2-Y and Si-HfO2-Yb. In the bonding layer, part of hafnium dioxide (HfO2) reacts with SiO2 at high temperature to form a high-temperature thermally stable HfSiO4 phase, which has a "pinning" effect in the coating, can deflect or even terminate microcracks, and improve the service life of the coating. At the same time, X solid dissolves into part of the HfO2 lattice, causing HfO2 to transform from m phase to c phase, which has a lower thermal conductivity at high temperature and can play a certain role in thermal protection for the CMCs matrix.
[0032] In an embodiment of the present invention, the molar ratio of Si, HfO2 and X in the bonding layer is preferably 50-60:25-35:5-25, more preferably 50-55:25-30:15-25, such as 50:25:25, 50:30:20, 55:25:20 or 55:30:15, preferably a range value with any of the above values as the upper or lower limit. The thickness of the Si-HfO2-X bonding layer is preferably 20-40 μm, more preferably 30-40 μm. Through the innovative research of the present invention, the Si-HfO2-X bonding layer of the above composition and thickness can inhibit the initiation and expansion of internal cracks in the coating during service, and at the same time provide a certain thermal protection effect for the CMCs substrate.
[0033] In an embodiment of the present invention, the Yb2Si2O7 environmental barrier layer 3 is in contact with the other side of the Si-HfO2-X bonding layer 2, and the composition of the Yb2Si2O7 environmental barrier layer 3 is ytterbium silicate (Yb2Si2O7). The thickness of the Yb2Si2O7 environmental barrier layer is preferably 30 to 50 μm, and more preferably 40 to 50 μm. This study unexpectedly found that the Yb2Si2O7 environmental barrier layer in the above thickness range has good thermal matching and chemical compatibility with the entire thermal environmental barrier coating system.
[0034] In an embodiment of the present invention, (RE1 m RE2 1-m )2Zr2O7 thermal barrier layer 4 contacts a surface of Yb2Si2O7 environmental barrier layer 3, RE1 and RE2 are respectively one of gadolinium (Gd), ytterbium (Yb), lanthanum (La), dysprosium (Dy), samarium (Sm), and neodymium (Nd); m is the atomic percentage, between 0 and 1, and the two rare earth elements are different. In some embodiments, the thermal barrier layer is composed of (Gd 0.9 Yb 0.1 )2Zr2O7、(La 0.7 G 0.3 )2Zr2O7、(Nd 0.8 Yb 0.2 )2Zr2O7、(Sm 0.7 Yb 0.3 )2Zr2O7、(Sm 0.9 G 0.1 )2Zr2O7. m RE2 1-m The thickness of the 2Zr2O7 thermal barrier layer is preferably 40 to 60 μm, more preferably 50 to 60 μm. m RE2 1-m )2Zr2O7 thermal barrier surface layer has excellent high-temperature corrosion resistance (water oxygen, CMAS, molten salt, etc.) and low thermal conductivity, which can bring good high-temperature corrosion protection effect to the CMCs matrix.
[0035] Moreover, the Yb2Si2O7 environmental barrier layer 3 described in the embodiment of the present invention can alleviate the Si-HfO2-X bonding layer 2 and (RE1 m RE2 1-m )2Zr2O7 thermal barrier layer 4 has a thermal mismatch, and its thermal expansion coefficient is between Si-HfO2-X and (RE1 m RE2 1-m)2Zr2O7, which is beneficial to slow down the accumulation of thermal stress during the hot and cold cycle. On the other hand, Yb2Si2O7 can react with Si-HfO2-X and (RE1 m RE2 1-m )2Zr2O7 maintains long-term chemical stability, so that the entire EBCs system has good chemical compatibility. Further, the (RE1 m RE2 1-m )2Zr2O7 thermal barrier surface layer has a columnar crystal structure and higher strain tolerance.
[0036] The thermal barrier coating described in the embodiment of the present invention may have a relatively small thickness, which is called a small thickness thermal barrier coating, etc. In some embodiments, the internal porosity of the thermal barrier surface layer is less than 2%, and the internal porosity of the bonding layer and the Yb2Si2O7 environmental barrier layer is less than 5%.
[0037] In some embodiments, the thermal environmental barrier coating may include, from the substrate to the outside, a Si-HfO2-X bonding layer with a thickness of 20 to 40 μm, a Yb2Si2O7 environmental barrier layer with a thickness of 30 to 50 μm, and a (RE1 m RE2 1-m )2Zr2O7 thermal barrier surface layer; the thermal barrier coating has a thickness of no more than 150μm, has a high bonding strength with the CMC substrate, and has excellent high temperature corrosion resistance at 1350℃, which is conducive to application.
[0038] The present invention provides a method for preparing a thermal environmental barrier coating for a small-thickness ceramic-based composite material as described above, comprising: forming a bonding layer, an environmental barrier layer and a thermal barrier surface layer in sequence from corresponding raw material powders by thermal spraying and / or physical vapor deposition on the surface of a base material, and obtaining a thermal environmental barrier coating for a small-thickness ceramic-based composite material through heat treatment.
[0039] See also Figure 2 As shown in the flow chart, the method for preparing the thermal environment barrier coating further comprises the following steps:
[0040] S1. Pre-treatment of the ceramic matrix composite material CMC substrate by sandblasting is preferred to facilitate coating processing;
[0041] S2. Using atmospheric plasma spraying technology, a Si-HfO2-X bonding layer and a Yb2Si2O7 environmental barrier layer are sequentially prepared on the surface of the pretreated ceramic matrix composite material substrate;
[0042] S3, using electron beam physical vapor deposition technology, on the surface of Yb2Si2O7 environmental barrier layer (RE1 m RE2 1-m )2Zr2O7 thermal barrier layer (also expressed as (RE1x RE2 1-x )2Zr2O7);
[0043] S4. Perform high-temperature heat treatment on the prepared three-layer coating on the substrate to obtain a thermal barrier coating for a small-thickness ceramic-based composite material.
[0044] In the embodiment of the present invention, the matrix material is the same as the matrix material described above, and no further description is given here. The ceramic matrix composite matrix is pretreated in the embodiment of the present invention as follows:
[0045] 1) The substrate material is ultrasonically cleaned in acetone to remove dirt, and then placed in an oven to dry at 100-120° C. for 15-30 minutes;
[0046] 2) The cleaned ceramic-based composite material substrate can be sandblasted using quartz sand of 100 to 300 meshes;
[0047] 3) Plasma jet heating is performed on the sandblasted ceramic-based composite material substrate to achieve a surface temperature of 400 to 600°C.
[0048] In the pretreatment process described in the embodiment of the present invention, the ultrasonic cleaning in acetone is preferably performed for 10 to 30 minutes, more preferably 15 to 20 minutes, to ensure sufficient cleaning.
[0049] In the pretreatment process described in the embodiment of the present invention, the drying temperature is preferably 100-120° C., more preferably 110-115° C., and the drying time is preferably 15-30 min, more preferably 20-25 min.
[0050] In the present invention, in order to increase the surface roughness of the ceramic-based composite material and thus improve the bonding force between the bonding layer and the substrate, the cleaned substrate can be sandblasted. Sandblasting is the process of cleaning and coarsening the surface of the substrate by the impact of high-speed sand flow. Compressed air can be used as a power to form a high-speed jet beam to spray the material (copper ore sand, quartz sand, corundum, iron sand, etc.) at high speed onto the surface of the workpiece to be processed, so that the appearance of the workpiece changes to a certain extent; due to the impact and cutting action of the material on the surface of the workpiece, the surface of the workpiece can obtain different roughness. The sandblasting treatment described in the embodiment of the present invention uses quartz sand, and the mesh number is preferably 100 to 300 meshes, more preferably 120 to 250 meshes; the pressure of sandblasting is preferably 0.1 to 0.5 MPa, more preferably 0.2 to 0.3 MPa, and the time of sandblasting is preferably 10 to 30 seconds, more preferably 15 to 25 seconds.
[0051] In the pretreatment process described in the embodiment of the present invention, the plasma jet heating is a common technical means in the art. After the plasma jet heating, the surface of the base material can be quickly heated to 400-600°C, preferably 500-600°C.
[0052] After obtaining the pretreated substrate material, the embodiment of the present invention adopts atmospheric plasma spraying technology to sequentially composite the Si-HfO2-X bonding layer and the Yb2Si2O7 environmental barrier layer on one surface thereof; then, preferably, electron beam physical vapor deposition technology is used to prepare (RE1 m RE2 1-m )2Zr2O7 thermal barrier surface layer.
[0053] Atmospheric plasma spraying (APS) is a plasma spraying method in thermal spraying process, which has the characteristics of high flame temperature and flexible process. The nozzle (anode) and electrode (cathode) of the plasma spray gun can be connected to the positive and negative poles of the power supply respectively, and the working gas is passed between the nozzle and the electrode, and the arc is ignited with the help of high-frequency sparks; the arc heats the gas and ionizes it to produce a plasma arc, and the gas expands thermally and ejects a high-speed plasma jet from the nozzle. The powder feeding gas feeds the raw material powder from the nozzle into the plasma jet, which is heated to a molten or semi-molten state, and then accelerated and sprayed onto the pre-treated workpiece surface to form a coating. Electron beam physical vapor deposition technology (EB-PVD) is a process of bombarding the deposition material (target material) with a high-energy density electron beam in a vacuum state, causing it to melt and evaporate, and condense and deposit on the substrate to form a coating.
[0054] The specific steps and parameters of the preparation method described in the embodiment of the present invention are as follows:
[0055] In the process of preparing the Si-HfO2-X bonding layer by atmospheric plasma spraying described in the embodiment of the present invention, argon and hydrogen are used as plasma, and the flow rate of argon is preferably 40-60 L / min, more preferably 45-55 L / min, such as 40 L / min, 45 L / min, 50 L / min, 55 L / min, 60 L / min, and preferably a range value with any of the above values as the upper or lower limit; the flow rate of hydrogen is preferably 5-12 L / min, more preferably 8-10 L / min, such as 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, and preferably a range value with any of the above values as the upper or lower limit.
[0056] The embodiment of the present invention uses Si-HfO2-X powder as the raw material for preparing the bonding layer, and the powder particle size is preferably 15-60μm, more preferably 15-45μm, such as 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, preferably a range value with any of the above values as the upper or lower limit.
[0057] The steps for preparing Si-HfO2-X powder in the embodiment of the present invention are as follows:
[0058] 1) first obtain HfO2-X powder by chemical coprecipitation method;
[0059] 2) mixing HfO2-X and Si powder by ball milling;
[0060] 3) The obtained Si-HfO2-X powder is sprayed and granulated, and then sintered at high temperature to obtain the product.
[0061] The Si—HfO2-X powder preparation process is a conventional process known to those skilled in the art, and the present invention does not impose any special limitation thereto, as long as the powder of the component can be obtained.
[0062] In an embodiment of the present invention, the distance of atmospheric plasma spraying of the bonding layer is preferably 80-150 mm, more preferably 100-120 mm, such as 80 mm, 90 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, preferably a range value with any of the above values as the upper or lower limit; the spraying current is preferably 300-600 A, more preferably 350-450 A, such as 300 A, 350 A, 400 A, 450 A, 500 A, 550 A, 600 A, preferably a range value with any of the above values as the upper or lower limit; the powder feeding rate is preferably 10-30 g / min, more preferably 15-25 g / min, such as 10 g / min, 15 g / min, 20 g / min, 25 g / min, 30 g / min, preferably a range value with any of the above values as the upper or lower limit.
[0063] In the process of preparing the Yb2Si2O7 environmental barrier layer by atmospheric plasma spraying, the embodiment of the present invention uses argon and hydrogen as plasma, and the flow rate of argon is preferably 40-80 L / min, more preferably 45-60 L / min, such as 40 L / min, 45 L / min, 50 L / min, 55 L / min, 60 L / min, 65 L / min, 70 L / min, 75 L / min, 80 L / min, and preferably a range value with any of the above values as the upper or lower limit; the flow rate of hydrogen is preferably 5-15 L / min, more preferably 8-12 L / min, such as 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, and preferably a range value with any of the above values as the upper or lower limit.
[0064] In the embodiment of the present invention, Yb2Si2O7 powder is preferably used to prepare the intermediate layer of the Yb2Si2O7 environmental barrier layer, which can be commercially available or prepared by oneself. In the preparation of the Yb2Si2O7 powder, ytterbium trioxide (Yb2O3) and SiO2 can be first ball-milled and mixed, then solid-phase sintered, and then spray granulated; this process is a conventional process known to those skilled in the art, and the present invention does not make any special limitation on this, as long as the powder of the component can be obtained.
[0065] In some embodiments, the particle size of the Yb2Si2O7 powder is preferably 15 to 45 μm, more preferably 15 to 30 μm, such as 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, preferably a range value with any of the above values as the upper or lower limit. The distance of the Yb2Si2O7 environmental barrier atmospheric plasma spraying is preferably 100 to 200 mm, more preferably 120 to 150 mm, such as 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, 160 mm, 170 mm, 180 mm, 190 mm, 200 mm, preferably a range value with any of the above values as the upper or lower limit; the spraying current is preferably 500 to 800 A, more preferably 550-650A, such as 500A, 550A, 600A, 650A, 700A, 750A, 800A, preferably a range value with any of the above values as the upper or lower limit; the powder feeding rate is preferably 10-30g / min, more preferably 15-25g / min, such as 110g / min, 15g / min, 20g / min, 25g / min, 30g / min, preferably a range value with any of the above values as the upper or lower limit.
[0066] The above step S3 is electron beam physical vapor deposition preparation (RE1m RE2 1-m )2Zr2O7 thermal barrier surface layer can not only ensure that the surface layer has a lower surface roughness and a higher density, but also has a columnar crystal structure, which can improve the strain tolerance. The specific steps of the process are as follows:
[0067] S31, providing preset components (RE1 m RE2 1-m )2Zr2O7 target material, the raw materials RE12O3, RE22O3 and ZrO2 can be mixed according to a set molar ratio and prepared by a high temperature solid phase reaction method (RE1 m RE2 1-m )2Zr2O7 composite powder; placing the composite powder in a stainless steel mold for pressing, the molding pressure is preferably 80-90KN, more preferably 85-90KN, such as 85KN or 90KN, preferably a range value with any of the above values as the upper or lower limit; the pressed block is sintered at a high temperature, the sintering temperature is preferably 1600℃-1800℃, more preferably 1700℃-1800℃, such as 1700℃, 1750℃, 1800℃, preferably a range value with any of the above values as the upper or lower limit; the sintering time is preferably 10h-20h, more preferably 16h-20h, such as 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, preferably a range value with any of the above values as the upper or lower limit, to obtain the corresponding target material;
[0068] S32, (RE1 m RE2 1-m )2Zr2O7 target material is loaded into the electron beam physical vapor deposition equipment and evaporated (RE1 m RE2 1-m )2Zr2O7 target, prepared on the surface of Yb2Si2O7 environmental barrier layer (RE1 m RE2 1-m )2Zr2O7 thermal barrier layer; wherein the evaporation current is preferably 1.2-1.8A, more preferably 1.5-1.8A, such as 1.2A, 1.3A, 1.4A, 1.5A, 1.6A, 1.7A, 1.8A, preferably a range value with any of the above values as the upper or lower limit; the substrate temperature is preferably 850°C-950°C, more preferably 900°C-950°C, such as 850°C, 900°C, 950°C, preferably a range value with any of the above values as the upper or lower limit; the vacuum degree is preferably ~10 -3 Pa; the deposition time is preferably 20-45min, more preferably 30-40min, such as 20min, 25min, 30min, 35min, 40min, 45min, preferably a range value with any of the above values as the upper or lower limit.
[0069] In the embodiment of the present invention, after the above three-layer structure coating is prepared by atmospheric plasma spraying and electron beam physical vapor deposition technology, the prepared thermal environment barrier coating is subjected to high-temperature heat treatment to obtain a thermal environment barrier coating for a small-thickness ceramic-based composite material.
[0070] The embodiment of the present invention can increase the bonding strength between the coating and the substrate through high-temperature heat treatment, and the prepared Yb2Si2O7 environmental barrier layer is an amorphous phase, and the amorphous phase can be crystallized after heat treatment, that is, crystallization. In an embodiment of the present invention, the high-temperature heat treatment is a vacuum heat treatment, and the temperature is preferably 1100-1300°C, more preferably 1200-1300°C, such as 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, preferably a range value with any of the above values as the upper or lower limit. The time of the high-temperature heat treatment is preferably 8-16h, more preferably 8-12 hours, such as 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, preferably a range value with any of the above values as the upper or lower limit.
[0071] The present invention also provides the above-mentioned small-thickness thermal environment barrier coating, which is used as a thermal protection coating on the surface of a ceramic-based composite material high-temperature component in an aeroengine.
[0072] The thermal environmental barrier coating prepared in the embodiment of the present invention is a multi-component multi-phase environmental barrier coating resistant to high temperature corrosion, and performance tests were conducted on it. The test contents are as follows.
[0073] High temperature water and oxygen corrosion performance test:
[0074] The method for assessing the resistance to water and oxygen corrosion is to conduct corrosion resistance tests in an environment of 1350°C, 90% H2O-10% O2, and 1atm until the coating shows obvious peeling (peeling area is greater than 10%), which is defined as failure.
[0075] High temperature CMAS corrosion resistance test:
[0076] The composition of CMAS is 33CaO-9MgO-13Al2O3-45SiO2 (mol.%), the test temperature is 1350°C, and the test time is 50h.
[0077] Thermal cycle performance test:
[0078] The thermal cycling performance assessment method is as follows: Refer to GJB 9876-2020 "Thermal Cycle Test Method for Thermal Barrier Coatings" and conduct a thermal cycling life test on the coating at 1300°C until the coating shows obvious peeling (peeling area greater than 10%), which is defined as failure.
[0079] In an embodiment of the present invention, the high-temperature component to which the thermal environmental barrier coating is applied is preferably a CMCs guide vane. The thickness of the third-generation EBCs system is generally 250-400 μm, and at 1350°C, the water-oxygen corrosion life of this system is approximately 600-700 hours. The small-thickness thermal environmental barrier coating described in the embodiment of the present invention has excellent high-temperature corrosion resistance (such as no peeling after 1000 hours of high-temperature water-oxygen corrosion), as well as high bonding strength, which is expected to reduce the weight of parts and reduce the impact of the coating on the throat area of parts while ensuring the service life of the hot end parts of ceramic-based composite materials.
[0080] In order to further illustrate the present invention, the thermal environment barrier coating provided by the present invention and its preparation method and application are described in detail below in combination with embodiments, but it should not be understood as limiting the protection scope of the present invention.
[0081] The Si-HfO2-X, Yb2Si2O7 powders and (RE1 m RE2 1-m )2Zr2O7 target materials can be obtained from the market. For example, the Si-HfO2-Y powder in this embodiment is prepared by Changsha College through chemical coprecipitation + spray granulation process, and Yb2S i2 O7 powder was purchased from Beijing Jiawa New Material Technology Co., Ltd. (Gd 0.9 Yb 0.1 )2Zr2O7 target was commissioned by Beijing University of Aeronautics and Astronautics to be prepared by high temperature solid phase reaction + cold pressing + high temperature sintering process. In addition, the powder and target preparation process are well known to those skilled in the art.
[0082] (Gd 0.9 Yb 0.1 )2Zr2O7 target material preparation: The raw materials Gd2O3, Yb2O3 and ZrO2 are mixed according to the set molar ratio and prepared by high temperature solid phase reaction method (Gd 0.9 Yb 0.1 )2Zr2O7 composite powder; the powder was placed in a stainless steel mold with an inner diameter of 68.5 mm, a height of 180 mm, and a molding pressure of 85 KN; the pressed block was sintered in a high-temperature furnace at 1700 ° C for 16 h to obtain (Gd 0.9 Yb .1 )2Zr2O7 target.
[0083] Example 1
[0084] (1) Preparation of SiC f The / SiC ceramic composite matrix specimen, with a size of 20 mm × 10 mm × 6 mm, was ultrasonically cleaned with acetone for 15 min and then placed in an oven to dry for 20 min at an oven temperature of 110 °C.
[0085] (2) For SiC f The SiC substrate was sandblasted before spraying, with 220-mesh quartz sand, 0.3 MPa sandblasting pressure and 15 s sandblasting time.
[0086] (3) SiC f The SiC substrate is installed on the automatic working table of the atmospheric plasma spraying equipment and is heated by the plasma flame flow to a surface temperature of 500°C.
[0087] (4) The powder particle size of 55Si-25HfO2-20Y (mol.%) after spray granulation is 15-45 μm, and the powder particle size of Yb2Si2O7 is 15-30 μm, and the powder after granulation is porous spherical powder; the above two powders are added to the powder feeder of the atmospheric plasma spraying equipment in sequence.
[0088] Atmospheric plasma spraying method is used on SiC f A 55Si-25HfO2-20Y bonding layer was prepared on the surface of the SiC substrate. The process parameters were adjusted as follows: argon flow rate was 45 L / min, hydrogen flow rate was 10 L / min, spraying distance was 110 mm, spraying current was 400 A, and powder feeding rate was 15 g / min, and a 55Si-25HfO2-20Y bonding layer with a thickness of 40 μm was obtained.
[0089] (5) An atmospheric plasma spraying method was used to prepare a Yb2Si2O7 environmental barrier layer on the surface of the 55Si-25HfO2-20Y bonding layer. The process parameters were adjusted as follows: the argon flow rate was 50 L / min, the hydrogen flow rate was 10 L / min, the spraying distance was 130 mm, the spraying current was 600 A, and the powder feeding rate was 20 g / min. A Yb2Si2O7 environmental barrier layer with a thickness of 50 μm was obtained.
[0090] (6) Electron beam physical vapor deposition was used to prepare (Gd 0.9 Yb 0.1 )2Zr2O7 thermal barrier layer, evaporation current is 1.5A, substrate temperature is 900℃, vacuum degree is ~10 -3 Pa, the deposition time was 30 min, and the thickness of (Gd 0.9 Yb 0.1 )2Zr2O7 thermal barrier surface layer.
[0091] (7) The deposited coating is heat treated by adjusting the process parameters as follows: temperature is 1200°C and time is 10 h.
[0092] The thermal environment barrier coating in Example 1 was subjected to a high temperature water-oxygen corrosion performance test. The results showed that the thermal environment barrier coating in this example did not peel off after 1000 hours of water-oxygen corrosion.
[0093] The thermal environment barrier coating in Example 1 was tested for its high temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was less than 25 μm and CMAS did not penetrate into the coating.
[0094] The thermal environment barrier coating in Example 1 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this example was greater than 1200 cycles.
[0095] Example 2
[0096] A thermal barrier coating for a ceramic matrix composite material with a small thickness was prepared according to the method in Example 1, except that:
[0097] In (4), the composition of Si-HfO2-X is 50Si-25HfO2-25Y (mol.%);
[0098] In (6), (Gd 0.9 Yb 0.1 )The thickness of the 2Zr2O7 thermal barrier layer is 50μm.
[0099] The microstructure of the coating obtained in Example 2 was detected by scanning electron microscopy. The results showed that the interfaces between the layers of the coating were tightly bonded, and no obvious cracks or holes were observed at the interfaces. 0.9 Yb 0.1 The internal porosity of the 2Zr2O7 thermal barrier layer is less than 2%, and the internal porosity of the 50Si-25HfO2-25Y bonding layer and the Yb2Si2O7 environmental barrier layer is less than 5%.
[0100] The thermal environment barrier coating in Example 2 was subjected to a high temperature water-oxygen corrosion performance test. The results showed that the thermal environment barrier coating in this example did not peel off after 1000 hours of water-oxygen corrosion.
[0101] The thermal environment barrier coating in Example 2 was tested for its high temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was less than 25 μm and CMAS did not penetrate into the coating.
[0102] The thermal environment barrier coating in Example 2 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this example was greater than 1200 cycles.
[0103] Example 3
[0104] A thermal barrier coating for a ceramic matrix composite material with a small thickness was prepared according to the method in Example 1, except that:
[0105] In (4), the thickness of the 55Si-25HfO2-20Y bonding layer is 30 μm;
[0106] In (5), the thickness of the Yb2Si2O7 environmental barrier layer is 40 μm.
[0107] The thermal environment barrier coating in Example 3 was subjected to a high temperature water-oxygen corrosion performance test. The results showed that the thermal environment barrier coating in this example did not peel off after 1000 hours of water-oxygen corrosion.
[0108] The thermal environment barrier coating in Example 3 was tested for its high temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was less than 25 μm and CMAS did not penetrate into the coating.
[0109] The thermal environment barrier coating in Example 3 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this example was greater than 1200 cycles.
[0110] Example 4
[0111] A thermal barrier coating for a ceramic matrix composite material with a small thickness was prepared according to the method in Example 1, except that:
[0112] In (4), the composition of Si-HfO2-X is 55Si-20HfO2-25Yb (mol.%).
[0113] According to GB / T 8642 2002 "Determination of tensile bonding strength of thermal spraying", the bonding strength of the coating obtained in Example 4 was tested (three groups of parallel samples were tested, recorded as Example 4-1, Example 4-2, and Example 4-3), and the results are shown in Table 1. It can be seen that the average bonding strength of the coating obtained in Example 4 is 24.1 MPa, indicating that the small thickness thermal environment barrier coating in the present invention has a strong bonding force with the substrate.
[0114] Table 1 Bonding strength of coating in Example 4
[0115] Sample Bonding strength (MPa) Example 4-1 23.1 Example 4-2 26.6 Example 4-3 22.6
[0116] The thermal environment barrier coating in Example 4 was subjected to a high temperature water-oxygen corrosion performance test. The results showed that the thermal environment barrier coating in this example did not peel off after 900 hours of water-oxygen corrosion.
[0117] The thermal environment barrier coating in Example 4 was tested for its high temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was less than 25 μm and CMAS did not penetrate into the coating.
[0118] The thermal environment barrier coating in Example 4 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this example was greater than 1200 cycles.
[0119] Example 5
[0120] The process of Example 5 is the same as that of Example 1, except that:
[0121] In (6), atmospheric plasma spraying method is used to prepare (Gd 0.9 Yb 0.1 )2Zr2O7 thermal barrier layer, the process parameters were adjusted as follows: argon flow rate of 55L / min, hydrogen flow rate of 12L / min, spraying distance of 130mm, spraying current of 600A, powder feeding rate of 25g / min, and a thickness of 60μm (Gd 0.9 Yb 0.1 )2Zr2O7 thermal barrier surface layer.
[0122] The thermal environment barrier coating in Example 5 was subjected to a high-temperature water-oxygen corrosion performance test. The results showed that the water-oxygen corrosion life of the thermal environment barrier coating in this example was approximately 616 hours.
[0123] The thermal environment barrier coating in Example 5 was tested for its high temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was greater than 30 μm and CMAS did not penetrate into the coating.
[0124] The thermal environment barrier coating in Example 5 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this example did not exceed 750 cycles.
[0125] Example 6
[0126] The process of Example 6 is the same as that of Example 1, except that:
[0127] In (5), the thickness of the Yb2Si2O7 environmental barrier layer is 100 μm;
[0128] In (6), (Gd 0.9 Yb 0.1 )2Zr2O7 thermal barrier layer thickness is 100μm.
[0129] The bonding strength of the coating prepared in Example 6 was tested according to GB / T 8642 2002 (three groups of parallel samples were tested, recorded as Example 6-1, Example 6-1, and Example 6-3), and the results are shown in Table 2. It can be seen that the average bonding strength of the coating prepared in Example 6 is 21.5 MPa, which is lower than that of the small thickness thermal barrier coating in Example 4.
[0130] Table 2 Bonding strength of coating in Example 6
[0131] Sample Bonding strength (MPa) Example 6-1 19.8 Example 6-2 20.8 Example 6-3 23.9
[0132] The thermal environment barrier coating in Example 6 was subjected to a high temperature water-oxygen corrosion performance test. The results showed that the thermal environment barrier coating in this example did not peel off after 1000 hours of water-oxygen corrosion.
[0133] The thermal environment barrier coating in Example 6 was tested for its high temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was less than 25 μm and CMAS did not penetrate into the coating.
[0134] The thermal environment barrier coating in Example 6 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this example was greater than 1000 cycles.
[0135] Comparative Example 1
[0136] Comparative Example 1 is the same as Example 1 except that:
[0137] In (4), Si powder of the same particle size is used to replace the 55Si-25HfO2-20Y powder in Example 1; an atmospheric plasma spraying method is used to coat SiC f A Si bonding layer with a thickness of 40 μm was prepared on the surface of the / SiC substrate.
[0138] The thermal environment barrier coating in comparative example 1 was subjected to a high-temperature water-oxygen corrosion performance test, and the results showed that the water-oxygen corrosion life of the thermal environment barrier coating in this embodiment does not exceed 650 hours.
[0139] The thermal environment barrier coating in Comparative Example 1 was tested for its high-temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was less than 25 μm and CMAS did not penetrate into the coating.
[0140] The thermal environmental barrier coating in Comparative Example 1 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the environmental barrier coating in this embodiment did not exceed 850 cycles.
[0141] Comparative Example 2
[0142] Comparative Example 2 is the same as Example 1, except that:
[0143] Electron beam physical vapor deposition technology was used to directly prepare (Gd 0.9 Yb 0.1 )2Zr2O7 thermal barrier layer, the coating thickness is 100μm.
[0144] The thermal environment barrier coating in Comparative Example 2 was subjected to a high-temperature water-oxygen corrosion performance test, and the results showed that the water-oxygen corrosion life of the thermal environment barrier coating in this embodiment does not exceed 300 hours.
[0145] The thermal environment barrier coating in Comparative Example 2 was tested for its high-temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was less than 25 μm and CMAS did not penetrate into the coating.
[0146] The thermal environment barrier coating in Comparative Example 2 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this embodiment did not exceed 300 cycles.
[0147] Comparative Example 3
[0148] Comparative Example 3 is the same as Example 1, except that:
[0149] The Yb2Si2O7 environmental barrier layer was prepared on the surface of the 55Si-25HfO2-20Y bonding layer by atmospheric plasma spraying. The coating thickness was 100 μm, and a 55Si-25HfO2-20Y / Yb2Si2O7 double-layer coating was obtained.
[0150] The thermal environment barrier coating in comparative example 3 was subjected to a high-temperature water-oxygen corrosion performance test, and the results showed that the water-oxygen corrosion life of the thermal environment barrier coating in this embodiment does not exceed 500 h.
[0151] The thermal environment barrier coating in Comparative Example 3 was tested for its high temperature CMAS corrosion resistance. The results showed that after 50 hours of corrosion, the thickness of the reaction layer was greater than 40 μm and CMAS did not penetrate into the coating.
[0152] The thermal environment barrier coating in Comparative Example 3 was subjected to a thermal cycle performance test, and the results showed that the thermal shock resistance life of the thermal environment barrier coating in this embodiment was greater than 1200 cycles.
[0153] From the above embodiments, it can be seen that the thermal environmental barrier coating of the preferred embodiment of the present invention may include, from the substrate to the outside, a Si-HfO2-X bonding layer with a thickness of 20 to 40 μm, a Yb2Si2O7 environmental barrier layer with a thickness of 30 to 50 μm, and a (RE1 m RE2 1-m )2Zr2O7 thermal barrier surface layer. The present invention mainly adopts atmospheric plasma spraying technology to prepare the bonding layer and environmental barrier layer, and adopts electron beam physical vapor deposition technology to prepare the thermal barrier surface layer. The small thickness thermal environmental barrier coating described in the present invention has excellent corrosion resistance and high bonding strength, and is expected to reduce the weight of parts and reduce the influence of the coating on the throat area of parts while ensuring the service life of the hot end parts of ceramic matrix composite materials.
[0154] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A thermal barrier coating for a thin-thickness ceramic-based composite material, characterized in that: It comprises a bonding layer, an environmental barrier layer and a thermal barrier surface layer in sequence, wherein the bonding layer is composed of Si-HfO2-X, wherein X is any one of Y, Yb, Gd and Er, and the bonding layer is in contact with the substrate; The composition of the environmental barrier layer is Yb2Si2O7; The composition of the thermal barrier surface layer is (RE1 m RE2 1-m )2Zr2O7, where RE1 and RE2 are respectively one of Gd, Yb, La, Dy, Sm and Nd, and m is the atomic percentage.
2. The thermal barrier coating for a ceramic matrix composite material with a small thickness according to claim 1, characterized in that: The molar ratio of Si, HfO2 and X in the bonding layer is 50-60:25-35:5-25.
3. The thermal barrier coating for a thin-thickness ceramic-based composite material according to claim 1, characterized in that: The thermal barrier surface layer has a columnar crystal structure.
4. The thermal barrier coating for a thin-thickness ceramic-based composite material according to any one of claims 1 to 3, characterized in that: The thickness of the bonding layer is 20-40 μm, the thickness of the environmental barrier layer is 30-50 μm, and the thickness of the thermal barrier surface layer is 40-60 μm.
5. The method for preparing a thermal barrier coating for a ceramic matrix composite material with a small thickness according to any one of claims 1 to 4, comprising the following steps: By means of thermal spraying and / or physical vapor deposition on the surface of the base material, the corresponding raw material powders are sequentially formed into a bonding layer, an environmental barrier layer and a thermal barrier surface layer, and after heat treatment, a thermal environmental barrier coating for a ceramic-based composite material with a small thickness is obtained.
6. The preparation method according to claim 5, characterized in that: The bonding layer is formed by atmospheric plasma spraying. During the spraying process, argon and hydrogen are used as plasma. The flow rate of argon is 40-60L / min, the flow rate of hydrogen is 5-15L / min, the spraying distance is 80-150mm, the spraying current is 300-600A, and the powder feeding rate is 10-30g / min. The raw material powder is Si-HfO2-X powder with a particle size of 15-60μm.
7. The preparation method according to claim 5, characterized in that: The environmental barrier layer is formed by atmospheric plasma spraying. During the spraying process, argon and hydrogen are used as plasma. The flow rate of argon is 40-80L / min, the flow rate of hydrogen is 5-15L / min, the spraying distance is 100-200mm, the spraying current is 500-800A, and the powder feeding rate is 10-30g / min. The raw material powder is Yb2Si2O7 powder with a particle size of 15-45μm.
8. The preparation method according to claim 5, characterized in that: The thermal barrier surface layer is formed by electron beam physical vapor deposition, and the electron beam physical vapor deposition process includes: m RE2 1-m )2Zr2O7 target material is loaded into an electron beam physical vapor deposition device, and a thermal barrier surface layer is formed on the surface of the environmental barrier layer by evaporating the target material. The evaporation current is 1.2-1.8A, the substrate temperature is 850°C-950°C, and the vacuum degree is 10 -3 Pa, the deposition time is 20 to 45 minutes.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The matrix material is a ceramic-based composite material; the preparation method further comprises pre-treating the ceramic-based composite material, wherein the pre-treatment comprises one or more of cleaning, sandblasting and plasma jet heating; The heat treatment temperature is 1100-1300° C. and the time is 8-16 hours.
10. Use of the thermal barrier coating according to any one of claims 1 to 4 as a thermal protection coating on the surface of high-temperature components of ceramic-based composite materials in aircraft engines.
Citation Information
Cited By
Environmental barrier coating and preparation method thereof
CN121344600A